PERCEPTION OF SPORTS TOURISM AWARENESS: AN EXAMINATION OF NIGERIA FANS' KNOWLEDGE AND INTEREST IN 2023 AFCON - AINA Stella Oluwatoyin Folajimi; OSUOHA Ifeanyi Jude; AREMU Samuel Olabisi; OLADAPO Olufunke; POPOOLA Esther Oyindamola (Scholars Digest Publishing, 2025)
This paper investigated the level of awareness and interest in sports tourism among Nigerian football fans during AFCON 2023. The research design adopted for this study is descriptive and survey-based, which enabled the systematic collection of primary data through the administration of a structured questionnaire. The study focused on a sample of 150 respondents, selected from various communities within the Local Government Area. Descriptive analysis was employed to analysis the data. Result from the study revealed that there is a high level of awareness among Nigerians of AFCON footballing competition. The level of education among Nigerians relate to awareness of the AFCON footballing competition. The ethnicity of Nigerians has an impact on the level of awareness of the AFCON footballing competition. The level of income among Nigerians relate to awareness of the AFCON footballing competition and that Nigerians rely on all information channels to get information about the AFCON footballing competition. The study therefore recommends that travel agencies and event organizers should create affordable and well-structured tour packages that combine match attendance with cultural and recreational activities.
Keywords: Sports, Tourism, Awareness, Interest, AFCON 2023, Fan Engagement.